Penanganan Kredit Bermasalah Pada Perumda BPR Bank Gresik - Aprilia, Nur Fitri; Akhiruddin, Anita (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Credit facilities are one of the services offered by BPR Bank Gresik, a financial organization that offers banking services to its customers. In providing this credit, BPR Bank Gresik experiences credit risk, namely credit is offered with interest that cannot be returned in accordance with the agreement that has been approved by the creditor and debtor. In bank financial management, problematic credit, or non-functioning credit, is a big problem. BPR Bank Gresik experienced various levels of problematic credit over the last five years, from 2018 to 2022. Improper credit management can result in losses. This research aims to overcome problem loans at